A cost effective energy saving of fluorescent lighting in commercial buildings - Lee, S.; Nayar, Chemmangot (2012)
Lighting represents a significant component of commercial buildings, particularly office buildings. Fluorescent lighting is invariably used in all commercial, industrial and residential areas. A significant amount of lighting energy is wasted every day by leaving the lights on and not utilizing daylight energy. However, if daylight illuminance can be harnessed, this will reduce the electricity consumption of fluorescent lamps and save energy. This paper explains possible significant savings in lighting energy consumption and hence in costs, without reducing the performance and visual satisfaction in office or industrial buildings. It is proposed to obtain energy saving by reducing the supply voltage without degradation in lighting performance. Experimental results confirm that as much as 20% of electrical energy can be saved by reducing about 9% of the supply voltage, without noticeably affecting light output while complying with lighting standard limits.